2009
DOI: 10.1016/j.carpath.2007.11.004
|View full text |Cite
|
Sign up to set email alerts
|

Role of carbonic anhydrase II in ectopic calcification

Abstract: These results indicate that CAR2 expression is an important regulator of ectopic calcification, potentially by facilitating OPN mediated mineral regression.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2012
2012
2015
2015

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 22 publications
0
9
0
Order By: Relevance
“…Thus, it is possible that CAVIII plays a role in forming the otic capsule and modiolus by modulating IP3‐induced Ca 2+ release during osteoblast differentiation. Although this hypothesis remains to be tested, Car8 expression in the differentiating otic capsule and modiolus is interesting because only Car1 and Car2 , which are expressed in bone marrow cells in otic capsule, have been known as major carbonic anhydrases associated with bone development (Lehenkari et al, ; Rajachar et al, ).…”
Section: Resultsmentioning
confidence: 99%
“…Thus, it is possible that CAVIII plays a role in forming the otic capsule and modiolus by modulating IP3‐induced Ca 2+ release during osteoblast differentiation. Although this hypothesis remains to be tested, Car8 expression in the differentiating otic capsule and modiolus is interesting because only Car1 and Car2 , which are expressed in bone marrow cells in otic capsule, have been known as major carbonic anhydrases associated with bone development (Lehenkari et al, ; Rajachar et al, ).…”
Section: Resultsmentioning
confidence: 99%
“…The ability of OPN to inhibit bioprosthetic valve calcification depends on its ability to bind to nascent mineral deposits via phosphorylated serine and threonine residues, thus blocking crystal growth (Jono et al, 2000). OPN also promotes RGD‐dependent cell interactions that lead to increased carbonic anhydrase expression and mineral regression (Rajachar et al, 2009; Steitz et al, 2002).…”
Section: Approaches To Diminish or Control The Fbrmentioning
confidence: 99%
“…Carbonic anhydrase, an enzyme that regulates ectopic calcification (64), as occurs in many AAA patients, may also serve as an autoantigen. In a proteomic survey of AAA walls by Ando et al (3), carbonic anhydrase 1 (CA1) was identified as a candidate autoantigen.…”
Section: Putative Autoantigens In Aaa Tissuementioning
confidence: 99%